Brício de Abreu e o jornal literário Dom Casmurro - Luca, Tania Regina de [UNESP] (Universidade Federal de Minas Gerais, Faculdade de Filosofia e Ciências Humanas, Departamento de História, 2013)
This paper analyses, in a preliminary way, the literary newspaper Dom Casmurro, published between 1937 and 1946, in Rio de Janeiro. We present the writers responsible for the project, objectives, the main features of the publication and its trajectory, which experienced significant change from 1942 onwards. On the other hand, it is also possible to interrogate about the role played by Dom Casmurro regarding aspects of the culture and history of the press, during the period of circulation.

O objetivo desse artigo é analisar, ainda de maneira preliminar, o jornal literário Dom Casmurro, que circulou entre 1937 e 1946 na cidade do Rio de Janeiro. Apresentam-se os responsáveis, objetivos e principais características do periódico, bem como sua trajetória, que conheceu significativa inflexão a partir de 1942. Pretende-se evidenciar a importância da publicação para a compreensão de aspectos do mundo da cultura e da história da imprensa, no referido período.
Brício de Abreu and the literary journal Dom Casmurro
Keywords: Dom Casmurro; Brício de Abreu; história da imprensa; Dom Casmurro; Brício de Abreu; history of the press